2004
DOI: 10.1111/j.1600-051x.2004.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases, their physiological inhibitors and osteoclast factors are differentially regulated by the cytokine profile in human periodontal disease

Abstract: It is possible that the pattern of cytokines expressed determines the stable or progressive nature of the lesions and regulates the severity of PD, driving the balance between MMPs and TIMPs, RANKL and OPG expression in the gingival tissues controlling the breakdown of soft and bone tissues and, consequently, the disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
241
1
22

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(275 citation statements)
references
References 59 publications
(73 reference statements)
11
241
1
22
Order By: Relevance
“…Furthermore, the increased ePD severity correlates with the significant increase in the levels of RANKL and MMP-13, and with the increase of RANKL/OPG and MMP-13/TIMPs ratios, characteristically associated with periodontal destruction. 13,19,45 Looking for the reason of the altered adaptive response because of RA/ PD interaction, we found that the submandibular LNs (the major draining LNs of oral cavity), which are significantly enlarged by the ePD induction, presented an even higher enlargement because of the pristane injection (data not shown), being an indicative of systemic immune reactivity to the PIA. Furthermore, the pattern of the transcription factors responsible for T-cell polarization expressed in submandibular LN was modulated by the PIA, the levels of Tbet and RORg being significantly increased in AIRmax mice submitted to both PIA and ePD protocols.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 90%
“…Furthermore, the increased ePD severity correlates with the significant increase in the levels of RANKL and MMP-13, and with the increase of RANKL/OPG and MMP-13/TIMPs ratios, characteristically associated with periodontal destruction. 13,19,45 Looking for the reason of the altered adaptive response because of RA/ PD interaction, we found that the submandibular LNs (the major draining LNs of oral cavity), which are significantly enlarged by the ePD induction, presented an even higher enlargement because of the pristane injection (data not shown), being an indicative of systemic immune reactivity to the PIA. Furthermore, the pattern of the transcription factors responsible for T-cell polarization expressed in submandibular LN was modulated by the PIA, the levels of Tbet and RORg being significantly increased in AIRmax mice submitted to both PIA and ePD protocols.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 90%
“…ECM turnover is clearly involved during bone remodeling and matrix metalloproteinases (MMPs) govern these events (7). MMPs are zinc-dependent endopeptidases.…”
Section: Fluoride Modulates Preosteoblasts Viability Andmentioning
confidence: 99%
“…Cytokines such as interleukin-1, tumor necrosis factor-, prostaglandin E2, and more recently adipokines, leptin, have been shown to orchestrate the host response to infectious and inflammatory stimuli. 1 Hence, the present study was designed to assess the concentration of human leptin in gingival crevicular fluid (GCF) and serum and to find out their link, if any, in periodontal health and disease; further, to get deeper insight into its possible role in commencement and development of periodontal disease.…”
Section: 5005/jp-journals-10029-1023mentioning
confidence: 99%